Critical Health Literacy in 3D - Renwick, Kerry (Frontiers in Education, 2017)
Literacy is increasingly being thought of as a social practice with its use and understandings being context dependent. As an essential element within and of education, literacy offers possibilities for engaging in everyday life. Health literacy has emerged as a means to develop health-promoting practices that has meaning in social contexts. Reflecting biomedical interests, the focus of health literacy is predominately constructed as a neutral and technical process that has specific meaning and practice, positioning it as functional literacy. This paper presents one approach to critical health literacy based on a multi-dimension (3D) approach that presents literacy as a situated social practice. The 3D model will be described and then the model’s application to health literacy will be explored. The use of the 3D model to build critical health literacy challenges the biomedical approach to health literacy as solely functional literacy. Functional literacy is not sufficient for a person to build a critical social consciousness and illuminate how social determinates of health create inequitable health or how it could be ameliorated. Social justice and equity are presented as fundamental pre-requisites for health. Working with young people in context of schools, the reciprocal relationship between health and education offers space for possibilities around literacy skills and understanding about what creates health. The same space can enable young people to see opportunities for empowerment to shape and recreate their social reality. Health literacy for social justice and equity therefore has to include possibilities for understanding and responding to socio-cultural knowing.